ANALISIS IMPLEMENTASI STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU MA MIFTAHUL HIDAYAH DI GAYAM LOR BONDOWOSO - Hoirotun; Surur, Miftahus; Puspitasari, Yesi (Yayasan Amanah Nur Aman, 2025)
This study analyzes the application of the principal's leadership strategy in improving the performance of MA Miftahul Hidayah Gayam Lor Bondowoso teachers. The method used is descriptive qualitative, which involves observation and interviews with the principal and teachers of MA Miftahul Hidayah as well as documentation. The results showed that effective leadership strategies in the form of fostering teachers' abilities, increasing discipline and motivation and implementing a comprehensive approach, have succeeded in improving teacher performance. However, there are some obstacles such as inadequate facilities, different levels of skills and experience among teachers, sometimes ineffective communication and lack of participation of school community members. This research is expected to contribute to the development of educational leadership in MA Miftahul Hidayah and other educational institutions.